PROBLEMATIKA ETIKA KOMUNIKASI PRIVASI PADA FILM "UNLOCKED" TAHUN 2023 - Mulzakir; Syafruddin Pohan; Al Hafizh M; Eliza Dwi Anggraeni (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study aims to investigate the representation and ethical dilemmas of privacy communication in the Korean film "Unlocked," which is popular on the Netflix streaming platform. In an intense and suspenseful story, the film follows Lee Na Mi, an ordinary office worker, who loses her mobile phone and ha\s to deal with serious consequences when her phone is hacked by Oh Jun Yeong, a psychopathic hacker. The research approach used Roland Barthes' semiotic analysis method and content analysis to identify semiotic elements in the film related to privacy communication ethics, through 3 stages namely denotation, connotation and Myth. The researcher collected 9 scenes from this film that illustrate the violation of Privacy Communication. The results reveal how the film uses visual signs, dialogue, and narration to convey complex messages about individual privacy rights in an increasingly sophisticated digital era. 6 points of privacy violation were found, namely: 1). handing over personal mobile phone user passwords on the grounds of mobile phone repair needs, 2). installation of cameras and illegal applications on mobile phones without permission which are used to stalk daily activities 3). hacking of personal data ranging from home door security codes, ATM PINs to media passwords, 4). entering the hacking victim's home without permission 5). Taking money from other people's ATMs without permission, 6). pretending to be someone else and provoking by uploading false information.